True brachial artery aneurysm after arteriovenous fistula closure following renal transplantation: a case report and literature review - Satoshi Toyota; Kentaro Inoue; Shun Kurose; Shinichiro Yoshino; Ken Nakayama; Sho Yamashita; Koichi Morisaki; Tadashi Furuyama; Masaki Mori (Surgical Case Reports)
Abstract Background A brachial artery aneurysm (BAA) is a rare condition accounting for 5% of all peripheral arterial aneurysms. More cases of true BAAs after arteriovenous fistula (AVF) closure have been reported in the past two decades. Case presentation A 60-year-old man who underwent AVF closure after renal transplantation had a true BAA on his left elbow that had grown within the past 6 months. We successfully performed an open repair with end-to-end anastomosis. No complications occurred for 1 year. Conclusions High flow due to AVF and some collateral factors such as the use of steroids and immunosuppressants after renal transplantation, arteriosclerosis, and chronic mechanical stimulation might contribute to BAA formation.